Neonatal outcomes in subgroups of women with preterm prelabor rupture of membranes before 34 weeks. (17th July 2016) - Stepan, Martin; Cobo, Teresa; Maly, Jan; Navratilova, Martina; Musilova, Ivana; Hornychova, Helena; Jacobsson, Bo; Kacerovsky, Marian
Abstract: Objective : To evaluate the influence of microbial invasion of the amniotic cavity (MIAC) and histological chorioamnionitis (HCA) on short-term neonatal outcome in women with preterm prelabor rupture of membranes before 34 weeks of gestation. Methods : A prospective observational cohort study including 122 pregnant women with PPROM between 24+0 and 34+0. MIAC was defined as a positive PCR result for Ureaplasma species, Mycoplasma hominis and Chlamydia trachomatis and/or positive PCR result for the 16S rRNA gene in the amniotic fluid. HCA was defined according to the Salafia classification. Maternal and short-term neonatal outcomes were evaluated according to the presence or absence of MIAC and/or HCA. Results : The presence of both MIAC and HCA was observed in 36% (45/122) of women, HCA alone in 34% (41/122) and MIAC in 5% (6/122). A significantly higher incidence of early onset sepsis was observed in newborns born from women with both MIAC and HCA [33% (15/45)] compared with women with HCA alone [12% (5/41)] or MIAC alone [0% (0/6)] or women without MIAC or HCA detected [0% (0/30); p = 0.001]. Conclusions : The presence of both MIAC and HCA increases the risk of early onset sepsis in pregnancies complicated by preterm prelabor rupture of membranes before 34 weeks of gestation.